Analisis Kelayakan Finansial Usaha Anggur Purwogrape di Kecamatan Tegaldlimo Kabupaten Banyuwangi - Minuk Sri Haryati; Azwar Annas; Imama Nurus Izaati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
One of the Banyuwangi locations, Tegaldlimo sub-district, has the capacity to grow grapes. One company that grows grapes in Tegaldlimo District is Purwogrape. There is a big chance to boost farmers' incomes because of the growing market demand for grapes, both domestically and internationally. Nevertheless, a thorough financial feasibility analysis is necessary to ensure the long-term viability of the business. The primary goal of this study is to evaluate the financial growth of the Purwogrape grape business. The approach employed in this research involves cash flow analysis and an assessment of investment feasibility. The results showed that Purwogrape grape business in Tegaldlimo sub-district is financially viable. The NPV indicator showed a value of Rp1.089.451.177,-. The IRR value show 45%. The result of the payback period calculation is 2.380 or 2 years and 4 months. The B/C ratio findings indicate that the average value, 5.9, is higher than 0. Additionally, the R/C value is 2.0, which is more than 1 (R/C > 1), and the Gross B/C value is 1.8, which is more than one (Gross B/C > 1).